Exploring the Prevalence of Scabies Infestation among Madrasa Students in a Rural Area of Mymensingh District, Bangladesh (Community Based Medical Journal, 2025)
Scabies is a highly prevalent, neglected worldwide distributed disease of children as well as elderly population, attributed to overcrowding, low-socioeconomic status, close contact and lack of personal hygiene. A cross sectional, descriptive study was done among young madrasa students, in a rural area of Mymensingh district of Bangladesh, between July and October of 2022, to explore the prevalence of scabies. 178 students were enrolled in this study through purposive, random sampling method. Data were collected through direct interviewing of the respondents. Age of the participants ranged between 5 and 19 years with mean age 10.13±2.159 years; 10–14 years age group was predominate (52%). Female students (68%) were predominant over male students (32%). Male female ratio was 32:68. Primary level educated students were higher than the secondary level. 54% of the families of madrasa students were poor. A significant association (p